The perception and determinants of agricultural technology adaptation of teff producers to climate change in North Shewa zone, Amhara Regional State, Ethiopia - Girma Mulugata Emeru (Cogent Economics & Finance)
The ongoing climate change is vital to exert context-specific responses to allay its adverse effects. The purpose of this study is to examine the perception and determinants of agricultural technology adaptation of teff producers to climate change in North Shewa zone, Ethiopia. Data were collected from 378 farming households through a multistage and simple proportional sampling procedure. Both descriptive and econometric analyses were used in this study. A Heckman probit model and a multinomial logit (MNL) model are used to examine the determinants of perception and adaptation to climate change, respectively. The results of the Heckman probit model revealed that gender, farm experience, access to extension services and information access were found to have a significant influence on the probability of farmers to perceive and/or adapt to climate change. The multinomial logit models showed that education, gender of the household head being male, marital status, farming experience, income, access to information, livestock ownership, tenure status, and access to extension are the main factors that increase adaptive capacity. However, distance to the nearest market and family size negatively and significantly affect the decision to adopt various agricultural technologies. This study recommends that, Future development initiatives should focus on enhencing perception and scaling up climate change adaption technology, which calls for a public-private collaboration and a shared vision of all potential stakeholders.